APLIKASI METODE SIX SIGMA (DMAIC) UNTUK MENINGKATKAN RENDEMEN PROSES PRODUKSI KAYU LAPIS - Resta Rene Mondina; Emi Roslinda; Dina Setyawati (Tengkawang : Jurnal Ilmu Kehutanan, 2022)
The rendement value of plywood industry is a benchmark of increasing efficiency in utilizing raw materials. Raw materials from natural forests produced into plywood have a yield that is not in accordance with P.15/PHPL-PPHH/2015. The detailed and sequential DMAIC method can analyze the impact of the use of natural forest raw materials. The purpose of the research is to elaborate the application of six sigma (DMAIC) in PT. XYZ and prove the use of six sigma method can increase the yield of plywood production in PT. XYZ to conform to P.15/PHPL-PPHH/2015. The research was conducted in September-November 2020. This research uses six sigma method with DMAIC (Define, Measure, Analyze, Improve and Control) stages in each plywood production process. The results showed that the rendemen increased by 2.14% by applying the six sigma (DMAIC) method. These results were found based on the collection of define and measure data (analysis of waste problems and rendemen of each production process and interviews), processing of analyze and improve data (analysis of causes and proposed problems of low rendemen value) and implementation of data control (analysis on three production processes of low rendemen causes). The proposed improvement is minimalism tearing of finir core at rotary process, so that there is an increase in plywood production rendemen from 88.23% to 90.37%.Keywords : six sigma (DMAIC), rendement, process, plywoodAbstrakNilai rendemen industri kayu lapis merupakan tolak ukur tentang peningkatan efisiensi dalam memanfaatkan bahan baku. Bahan baku dari hutan alam diproduksi menjadi kayu lapis memiliki rendemen yang tidak sesuai dengan P.15/PHPL-PPHH/2015. Penerapan metode DMAIC yang detail dan berurutan dapat menganalisa dampak dari penggunaan bahan baku hutan alam. Tujuan penelitian adalah menguraikan penerapan six sigma model DMAIC di PT. XYZ dan membuktikan penggunaan metode six sigma dapat meningkatkan rendemen produksi kayu lapis di PT. XYZ agar sesuai dengan P.15/PHPL-PPHH/2015(P_15_2015 Efisiensi Bahan Baku_zgZVDf, n.d.). Penelitian dilaksanakan pada September-November 2020. Penelitian ini menggunakan metode six sigma dengan tahapan DMAIC (Define, Measure, Analyze, Improve dan Control) pada setiap proses produksi kayu lapis. Hasil penelitian menunjukkan bahwa rendemen meningkat sebesar 2,14% dengan menerapkan metode six sigma (DMAIC). Hasil ini ditemukan berdasarkan pengumpulan data define dan measure (analisis masalah limbah dan rendemen setiap proses produksi serta wawancara), pengolahan data analyze dan improve (analisis penyebab dan usulan masalah nilai rendemen rendah) serta implementasi data control (analisis pada tiga proses produksi penyebab rendemen rendah). Perbaikan yang diusulkan adalah minimalisir penyobekan finir core proses rotary, sehingga terjadi peningkatan rendemen produksi kayu lapis dari 88,23% menjadi 90,37%.Kata kunci : six sigma (DMAIC), rendemen, proses, kayu lapis